2020
DOI: 10.1176/appi.ps.201900399
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Investigation of Engagement in Mental Health Services Among Black and Hispanic LGB Young Adults

Abstract: Objective: Little attention has been paid to engagement in mental health services among racially and ethnically diverse youths who identify as a sexual minority, despite research indicating that they face significant mental health disparities. In this study, the authors assessed the service use experiences of black and Hispanic lesbian, gay, and bisexual (LGB) young adults to identify factors that promoted or hindered their engagement.Methods: Semistructured interviews with 38 young adults regarding past and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…There are limitations to this approach, however. Individual clinician competency can vary, and as youth may engage with multiple service providers within a given organization, there is risk or perception of risk of having their identity stigmatized by providers, which may result in a youth not disclosing their identity or acting as a barrier to seeking out support (Moore et al, 2020). There can also be risk or anticipation of risk of experiencing discrimination and harassment from other participants such as in the waiting room or in group settings which may act as a barrier to care (Cochran, Peavy, & Cauce, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are limitations to this approach, however. Individual clinician competency can vary, and as youth may engage with multiple service providers within a given organization, there is risk or perception of risk of having their identity stigmatized by providers, which may result in a youth not disclosing their identity or acting as a barrier to seeking out support (Moore et al, 2020). There can also be risk or anticipation of risk of experiencing discrimination and harassment from other participants such as in the waiting room or in group settings which may act as a barrier to care (Cochran, Peavy, & Cauce, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…LGBTQ2S+ young adults identi ed several additional barriers, including stigma associated with mental health symptoms and sexuality, ambivalence about the e cacy of treatment, and lack of family support due to family's previous negative experiences with mental health interventions (Moore, Lopez, Camacho, & Munson, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Specific ethnic, cultural, and sexual minority populations were also under-represented, and their reasons for engagement and disengagement may vary. Moore et al’s US study of engagement among Black and Hispanic LGB young adults [ 32 ], for example, found stigma related to sexual orientation and cultural attitudes, ambivalence about treatment efficacy, lack of family support, and difficulty finding suitable and affordable care were important barriers.…”
Section: Discussionmentioning
confidence: 99%
“…provider mistrust (Ferlatte et al, 2019;Moore et al, 2020) and other barriers to accessing LGBTQ-affirmative services (Veltman & Chaimowitz, 2014). LGBTQ individuals' negative interactions with providers have been associated with reduced health care engagement (James et al, 2016;Li et al, 2015), while lack of LGBTQ-specific or affirming expertise often results in inadequate and/or withheld treatment (Calabrese et al, 2018;James et al, 2016).…”
mentioning
confidence: 99%
“…Stigma generates excess stress and depletes coping abilities for lesbian, gay, bisexual, transgender, and queer (LGBTQ) individuals worldwide (Mays & Cochran, 2001; Meyer et al, 2008) and is associated with adverse physical (Kecojevic et al, 2012; Poteat et al, 2018) and mental health (Ferlatte et al, 2019; Shipherd et al, 2010; Wilton et al, 2018). In mental health care contexts, stigma generates provider mistrust (Ferlatte et al, 2019; Moore et al, 2020) and other barriers to accessing LGBTQ-affirmative services (Veltman & Chaimowitz, 2014). LGBTQ individuals’ negative interactions with providers have been associated with reduced health care engagement (James et al, 2016; Li et al, 2015), while lack of LGBTQ-specific or affirming expertise often results in inadequate and/or withheld treatment (Calabrese et al, 2018; James et al, 2016).…”
mentioning
confidence: 99%